Fungicidal activity of the nanoemulsion (o/w) of origanum vulgare essential oil (Research, Society and Development, 2023)
This study aimed to evaluate the fungicidal activity of the nanoemulsion (O/W) of the essential oil of Origanum vulgare. Origanum vulgare leaf samples were collected in the morning in the city of São Luís (MA). To extract the essential oil, the hydrodistillation technique was used. The essential oil constituents were identified by Gas Chromatography Coupled to Mass Spectrometry (GC-MS). Nanoemulsions were prepared by phase inversion method. The antimicrobial activity was performed by the disk diffusion technique according to the Clinical and Laboratory Standards Institute (2020). According to the GC-MS, 25 chemical constituents were identified, the majority being carvacrol corresponding to 66.36%. The formulated nanoemulsion was characterized as an oil-in-water nanoemulsion, and also evaluated as a stable formulation. The nanoemulsion of Origanum vulgare showed fungicidal activity against the fungi tested and its best result was a potent anti-candida efficacy. Finally, the results obtained indicate great potential for the use of essential oils in the formulation of nanoemulsions used in this study as fungicidal agents.